A Case of Congenitally Corrected Transposition of Great Arteries: An Infrequent Happenstance - Prakash Ajmera; Vikas Medep (Case Reports in Medicine)
Congenitally corrected transposition of the great arteries (CCTGA) is rare form of congenital heart diseases. It may be present with or without associated anomalies. Patients with CCTGA are usually diagnosed at early stages of life due to associated anomalies, but they may even remain asymptomatic till later decades of their life. We report a case of a 42-year-old man who presented at neurosurgery department with dizziness, seizures, and loss of consciousness, in whom isolated CCTGA was discovered incidentally. Further investigation depicted right ventricular hypertrophy, mild valvular regurgitation, mildly dilated pulmonary artery, low heart rate with AV dissociation, and third-degree heart block. These indicated for implantation of permanent pacemaker into the patient. The implantation of VVI mode pacemaker was uneventful and the patient is being followed up in the past eight months in favorable condition.